Denmark : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 1999)
This 1999 Article IV Consultation highlights that the Danish economy continued to perform well in 1997-98. Real GDP growth of about 3 percent remained above potential and unemployment fell to 6 percent, less than half its level only five years earlier. Consumer price inflation remained subdued at slightly below 2 percent. However, capacity constraints became more evident and the external current account balance showed a deficit-for the first time since 1989-of 1.4 percent of GDP. Also, at 4 1\2 percent, wage inflation remained higher than in the main trading partner countries.